2003
DOI: 10.1016/s0741-5214(03)00774-2
|View full text |Cite
|
Sign up to set email alerts
|

Transbrachial arterial insertion of aortic occlusion balloon catheter in patients with shock from ruptured abdominal aortic aneurysm

Abstract: Transbrachial arterial insertion of an AOBC may be useful to ameliorate hemorrhagic shock in patients with ruptured AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 18 publications
0
23
2
1
Order By: Relevance
“…The three patients required amputation. Other investigators have noted that some patients treated with IABO developed complications of balloon rupture . However, there were no complications related to the use of IABO in the present study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The three patients required amputation. Other investigators have noted that some patients treated with IABO developed complications of balloon rupture . However, there were no complications related to the use of IABO in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, the SBP values increased in all patients after IABO; the mean SBP increased from 75 ± 10 mmHg to 124 ± 22 mmHg. Some authors have already reported similarly significant mean increases in SBP after IABO, allowing for the control of hemorrhagic shock . Irahara et al .…”
Section: Discussionmentioning
confidence: 83%
“…6 More recently, endovascular approach has emerged in the management algorithm of some vascular emergencies, including acute aneurysm rupture. 7 Results of aortic balloon occlusion (ABO) as for damage control in animal models of severe abdominal trauma with hemorrhage are contrasting, 8 -10 but several case reports have suggested the efficacy of the method. 11 The aim of this study was to evaluate the safety, hemodynamic effects, and metabolic consequences of an endovascular retrograde occlusion of the thoracic aorta in an experimental model of uncontrolled hemorrhagic shock caused by an abdominal trauma in pigs.…”
mentioning
confidence: 99%
“…Reports of transbrachial AOB placement have been described for RAAA, [12][13][14] and abdominal hemorrhage. 15 This technique may involve a cutdown procedure to access the brachial artery.…”
Section: Discussionmentioning
confidence: 99%